Simple and fast electrochemical detection of sequence-specific DNA via click chemistry-mediated labeling of hairpin DNA probes with ethynylferrocene. Issue 12 (21st June 2015) - Hu, Qiong; Deng, Xianbao; Kong, Jinming; Dong, Yuanyuan; Liu, Qianrui; Zhang, Xueji
<x xml:space="preserve">Abstract</x> In this work, the azido-containing hairpins were exploited as the capture probes; after hybridization, labeling of electroactive probes, ethynylferrocene, was conveniently and efficiently achieved via the Cu(i)-catalyzed azide–alkyne cycloaddition.